Problematic smartphone usage in the Austrian general population: a comparative study of 2022 and 2024, mental health correlates and sociodemographic risk factors - Humer, Elke; Zeldovich, Marina; Probst, Thomas; Pieh, Christoph (Frontiers in Public Health, 2025)
BackgroundThe increasing integration of smartphones into daily life raises concerns about potential mental health impacts associated with excessive usage. This study aimed to assess trends in smartphone usage and examine its association with mental health issues as well as to assess sociodemographic risk factors for problematic smartphone usage in the Austrian population over two periods, 2022 and 2024.MethodsTwo cross-sectional online surveys were conducted with representative samples of the Austrian general population (N = 3,057). Sociodemographic data, smartphone usage patterns, and mental health indicators, including clinically relevant depression, anxiety, insomnia, alcohol abuse, and high stress, were collected. Problematic smartphone use was defined as usage of at least 3 h per day. Chi-squared tests and multivariable logistic regression models were applied to analyze associations.ResultsSmartphone usage increased significantly from 2022 to 2024, with a higher prevalence of problematic usage observed in 2024. Higher smartphone use was associated with increased odds of mental health issues, particularly for those spending at least 3 h daily on their phones. Women, younger participants, and Vienna residents showed a higher likelihood of problematic smartphone use.ConclusionThe marked increase in smartphone usage between 2022 and 2024, along with its association with mental health issues, highlights the need for public health interventions targeting digital well-being. Specific groups, notably younger individuals, women, and urban residents, may require targeted strategies to mitigate excessive smartphone usage.